Review of ecological effects of oil exploration in the Niger-Delta, Nigeria (2014)
A review was carried out on the ecological effects of oil exploration in the Niger-Delta region of Nigeria. The Niger-Delta is a vast bird foot-shaped floodplain and the World’s third largest delta. It is a geographical entity situated in the central part of Southern- Nigeria that is home to the oil-producing states of Nigeria. Oil activities and its ecological effects are discussed with remediation of affected sites. Sustainable development is recommended in the sector to boost the economy and meet the environmental quality aspirations of host communities